3′,4′-Dihydroxyflavonol reduces infarct size and injury associated with myocardial ischaemia and reperfusion in sheep - Wang, Sheng (2004)
1. The antioxidant properties of flavonols in vivo and their potential benefits in myocardial ischaemia/reperfusion (I/R) injury have been little investigated. We evaluated the ability of a synthetic flavonol, 3′,4′-dihydroxyflavonol (DiOHF) to scavenge superoxide in post-I/R myocardium and to prevent myocardial I/R injury. 2. Anaesthetized sheep were studied in four groups (n=5–6): control, ischaemic preconditioning (IPC), vehicle and DiOHF (before reperfusion, 5 mg kg(−1), i.v.). The left anterior descending coronary artery was occluded distal to the second diagonal branch for 1 h followed by 2 h of reperfusion. Infarct size, myocardial function, NADPH-activated superoxide generation and biochemical markers of injury were measured. 3. DiOHF (10(−8)–10(−4) M) incubated in vitro with post-I/R myocardium from the vehicle group suppressed superoxide production dose-dependently. DiOHF administered in vivo also significantly reduced superoxide generation in vitro. 4. DiOHF and IPC markedly reduced infarct size, which was 73±2% of the area at risk in vehicle, 50±4% in DiOHF, 75±5% in control and 44±4% in IPC. Post-I/R segment shortening within the ischaemic zone was greater in DiOHF (2.3±0.7%; P<0.01) and IPC (1.7±0.5%; P<0.01) than those in corresponding controls (−1.7±0.4; −2.1±0.4%). 5. DiOHF and IPC improved coronary blood flow to the ischaemic area and preserved higher levels of nitric oxide metabolites in the venous outflow from the ischaemic zone. 6. DiOHF attenuated superoxide production in post-I/R myocardium, and significantly reduced infarct size and injury following I/R in anaesthetized sheep. The extent of protection by DiOHF is comparable to that afforded by IPC. Thus, DiOHF has clinical potential for improving recovery from acute myocardial infarction and other ischaemic syndromes.